2019
DOI: 10.1108/oir-05-2018-0168
|View full text |Cite
|
Sign up to set email alerts
|

How can WeChat contribute to psychosocial benefits? Unpacking mechanisms underlying network size, social capital and life satisfaction among sojourners

Abstract: Purpose The purpose of this paper is to systematically unpack whether and how WeChat network size is correlated with perceived social capital and life satisfaction among Chinese overseas students in Germany. Design/methodology/approach Based on a web-based survey data collected from 218 sojourners, zero-order correlation analyses and structural equation modeling were separately implemented to tackle the complicated research questions. Findings Findings demonstrate that an individual’s WeChat network size s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 61 publications
5
27
0
Order By: Relevance
“…First, the significant outcomes for Hypotheses 2-3 corroborate the path effects suggesting that sharing and liking can positively influence bonding and bridging social capital. The results are in accordance with previous studies that identified social media use as a key factor contributing to individual's social capital in the computer-mediated environment [7,21,72]. Regarding seeking behavior, H1a is supported while H1b is rejected, showing that seeking only has effects on bonding social capital.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…First, the significant outcomes for Hypotheses 2-3 corroborate the path effects suggesting that sharing and liking can positively influence bonding and bridging social capital. The results are in accordance with previous studies that identified social media use as a key factor contributing to individual's social capital in the computer-mediated environment [7,21,72]. Regarding seeking behavior, H1a is supported while H1b is rejected, showing that seeking only has effects on bonding social capital.…”
Section: Resultssupporting
confidence: 91%
“…Drawing on social capital theory and previous studies on WeChat use behavior [7,14,27], this paper constructs a research model (presented in Figure 1) to systematically explore the factors that influence individuals' e-WOM intention. WeChat use behavior is further decomposed into seeking, sharing, and liking, and is expected to exert direct effects on social capital and e-WOM intention.…”
Section: Research Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…First, previous studies in China either selected specific population as the research object [ 24 , 25 ] or limited study area [ 15 , 26 ]. For example, Pang [ 27 ] investigated the impact of social capital on life satisfaction among Chinese overseas students in Germany and found that social capital is a significant predictor of life satisfaction. Yuan [ 28 ] only analyzed the impact of social capital on life satisfaction in three Chinese cities (Shanghai, Beijing, and Guangdong).…”
Section: Introductionmentioning
confidence: 99%
“…First, as one component of subjective well-being (Çikrıkci, 2016;Diener et al, 1985), life satisfaction reflects individuals' thoughts and feelings about their lives (Castellacii and Tveito, 2018;Diener and Diener, 1995;Liu et al, 2013). It is a judgmental process of how individuals evaluate the quality of their lives (Diener et al, 1985;Lim and Yang, 2019;Pang, 2019). Because the internet has become a part of most people's everyday lives (Fallows, 2004;Wellman and Haythornthwaite, 2002), prior research has suggested that psychological well-being and life satisfaction may be related to internet use (Castellacii and Tveito, 2018;Çikrıkci, 2016;Hofer et al, 2019).…”
Section: The Affective Aspectmentioning
confidence: 99%